Pengaruh Pola Susunan Laminasi Balok Bambu Tali (Gigantochloa apus Kurz) terhadap Kerapatan, Delaminasi dan Keteguhan Patah - Muhammad Faisal Mahdie; Andy Rinaldi (Jurnal Ilmu Kehutanan, 2007)
Effect of Lamination Pattern of Tali Bamboo (Gigantochloa apus Kurz) Beam  on Density, Delamination, And Rupture StrengthBamboo is a potential species as its price is relatively less expensive than wood logs while it also represents a fast growing plant and is easy to plant. In general bamboos in South Kalimantan have not been exploited optimally. Its utilization for construction purposes is very limited. This study aims to identify the effects of lamination pattern on the density, delamination and rupture impregnability (Modulus of Rupture, MoR) of laminated bamboo blocks, with the combinations of a (reed wall- reed wall), b (reed wall-husk), and c (husk- husk and reed wall-reed wall). The results showed that lamination patterns affected the density, delamination and rupture impregnability of the laminae produced. The average density (kg/cm3) is 0.5321, 0.6923, and 0.6746 for treatments a, b, and c respectively. Delamination percentage (%) is 6.55, 16.65, and 21.1, while the rupture impregnability level (kg/cm2) is 228.99, 152.09,and 171.97 for treatments a, b, and c respectively. Delamination percentage of less than 10%  suggets that the laminae produced can be used for building construction. that It is concluded that lamination pattern of reed wall-reed wall gave the best performance of bamboo lamina with the average density of 0.5321 kg/cm3, the delamination percentage of 6.55% , and the rupture impregnability level of 228.99 kg/cm2.